(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The health insurance industry in Haryana has undergone significant transformation in recent years due to national reforms, state-level initiatives, and the increasing participation of private insurers and third-party administrators. This study examines the current status of the industry by assessing awareness, accessibility, service quality, utilisation patterns, and operational challenges across public and private insurance providers. Using a mixed-methods approach involving surveys, structured interviews, and analysis of IRDAI reports, PM-JAY dashboards, and state databases, the research identifies critical gaps related to uneven hospital empanelment, beneficiary awareness, claim settlement delays, administrative inefficiencies, and urban–rural disparities. Findings reveal that while insurance penetration has expanded through PM-JAY, CHIRAYU Haryana, and private sector growth, service experience and utilisation remain inconsistent, with private providers performing better in customer service and claims responsiveness but public schemes offering stronger financial protection. The study highlights systemic barriers such as limited rural access, inadequate communication strategies, and strained provider–insurer relationships due to reimbursement delays. It demonstrates the need for integrated governance mechanisms, digital strengthening, improved monitoring systems, and targeted IEC campaigns to ensure equitable utilisation of insurance benefits. The research contributes to policy dialogue by presenting evidence-based insights into Haryana’s evolving insurance ecosystem and recommending strategic interventions for policymakers, insurers, and healthcare providers. It also identifies areas for future research, including comparative service quality assessments, district-level utilisation modelling, and post-COVID insurance behaviour shifts.